The Effectiveness of Art Therapy Approach Group Counseling in Reducing Academic Burnout in Tenth-grade High School Students - Johanna Ajeng; Ronny Gunawan; Evi Deliviana (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Tenth-grade students often face a variety of new tasks and demands that are denser and more rigorous. This triggers academic burnout. Therefore, this study aims to examine the effectiveness of an art therapy approach in group counseling for reducing academic burnout among tenth-grade students. Using a pretest-posttest quasi-experimental design with 10 samples of students with high levels of academic burnout. Data were collected using the School Burnout Inventory (SBI) administered before and after 5 sessions of intervention meetings. The results of the analysis showed a significant decrease (p = 0.002) in the level of academic burnout in the experimental group (mean 25.80) compared to the control group (mean 28.20). The intervention appears effective in reducing academic burnout. Based on this, schools are advised to consider the use of group counseling with an art therapy approach as an intervention to address academic burnout, with the expectation that it will improve emotional well-being and academic achievement. Keywords: group counseling, art therapy approach, academic burnout, tenth-grade students